Simulating bioclogging effects on dynamic riverbed permeability and infiltration. Issue 4 (17th April 2016) - Newcomer, Michelle E.; Hubbard, Susan S.; Fleckenstein, Jan H.; Maier, Ulrich; Schmidt, Christian; Thullner, Martin; Ulrich, Craig; Flipo, Nicolas; Rubin, Yoram
Abstract: Bioclogging in rivers can detrimentally impact aquifer recharge. This is particularly so in dry regions, where losing rivers are common, and where disconnection between surface water and groundwater (leading to the development of an unsaturated zone) can occur. Reduction in riverbed permeability due to biomass growth is a time‐variable parameter that is often neglected, yet permeability reduction from bioclogging can introduce order of magnitude changes in seepage fluxes from rivers over short (i.e., monthly) timescales. To address the combined effects of bioclogging and disconnection on infiltration, we developed numerical representations of bioclogging processes within a one‐dimensional, variably saturated flow model representing losing‐connected and losing‐disconnected rivers. We tested these formulations using a synthetic case study informed with biological data obtained from the Russian River, California, USA. Our findings show that modeled biomass growth reduced seepage for losing‐connected and losing‐disconnected rivers. However, for rivers undergoing disconnection, infiltration declines occurred only after the system was fully disconnected. Before full disconnection, biologically induced permeability declines were not significant enough to offset the infiltration gains introduced by disconnection. The two effects combine to lead to a characteristic infiltration curve where peak infiltration magnitude and timing is controlled by permeability declines relative to hydraulic gradient gains. Biomass growth was found to hasten the onset of full disconnection; a condition we term 'effective disconnection'. Our results show that river infiltration can respond dynamically to bioclogging and subsequent permeability declines that are highly dependent on river connection status. Key Points: Riverbed bioclogging is a key control on infiltration in losing rivers River infiltration gains from disconnection can offset riverbed permeability declines caused by bioclogging Permeability reduction can hasten the onset of disconnection